A Non-Scheduled Multi-Stage Decision-Making Approach to Control Cascading Failures - Liu, Yumeng; Wang, Tao; Guo, Jiayi (Frontiers in Energy Research, 2022)
The control research on cascading failures is critical to ensure the reliability of power supply. A path-driven multi-stage corrective control model for the whole process of cascading failures is established to eliminate the risk of cascading failure. For the cascading failure process caused by overloading, the selection criterion for subsequent outage is defined according to the mechanism of propagation of cascading failures. The path-driven constraints and power relaxation constraints are extracted based on the selection criterion for a subsequent outage. A model coupled with non-scheduled multi-stage decision-making is designed by considering the flexibility of control action implementation to optimize the sum of control cost and load-shedding risk for elimination of cascading failures. The verification results show that the proposed method can reduce the probability of outages of tripped branches and successfully eliminate cascading failure.